Clinical evaluation of the cobas® MTB-RIF/INH reagent and the cobas® 6800 for the detection of isoniazid and rifampicin resistance. (May 2022) - Aono, Akio; Murase, Yoshiro; Minegishi, Masaaki; Ohtawa, Shuichi; Yano, Masatoshi; Chikamatsu, Kinuyo; Shimomura, Yoshiko; Hosoya, Makiko; Igarashi, Yuriko; Morishige, Yuta; Yamada, Hiroyuki; Takaki, Akiko; et al.
Abstract: We aimed to validate the performance of a newly developed real-time PCR assay using cobas® MTB-RIF/INH reagent on the cobas® 6800 system for detecting isoniazid (INH) and rifampicin (RIF) resistance, using Japanese Mycobacterium tuberculosis (MTB) isolates. In total, 119 mock sputum specimens spiked with resistant MTB were tested using the cobas® MTB-RIF/INH reagent. The whole genomes of all MTB isolates were sequenced by MiSeq and analysed for mutations/indels causing drug resistance. All isolates were tested for phenotypic drug susceptibility, then MTB negative sputa were collected and pooled to prepare mock sputum specimens for the study. The sensitivity and specificity for INH resistance at a concentration equal to 3 × the limit of detection were 77.8% and 90.0%, respectively; those for RIF resistance were 91.8% and 93.5%, respectively. The sensitivities for INH and RIF were statistically different ( P  = 0.014), but not the specificities ( P = 0.624). Twenty-two false-susceptible and two false-resistant results were obtained in INH; meanwhile, six false-susceptible and three false-resistant results were obtained in RIF. False-resistance for INH and RIF was mainly due to disputed mutations. The cobas® MTB-RIF/INH reagent showed better performance than other rapid molecular tests.